PARADIGMA ULAMA DALAM MENENTUKAN KUALITAS HADIS DAN IMPLIKASINYA DALAM KEHIDUPAN UMAT ISLAM - Mujibatun, Siti (Universitas Islam Negeri Raden Intan Lampung, 2014)
THE SCHOLARS PARADIGM IN DETERMINING THE QUALITY OF THE HADITHAND ITS IMPLICATIONS FOR THE USE OF THE LEGAL BASIS IN THE DAILY LIFE OF MUSLIMS TODAY. The emergence of internal conflicts religious (Islam) in the practice of religion in daily life caused by the different sects among the hadith scholars since the early Islamic period to the present, especially in determining the quality of the hadith as evidence syar’iyyah. The scholars of Hadith have a typology and different concepts, so a significant impact on the use of different reference amaliah Muslims today. Even sometimes cause reactions mislead each other and each other infidel. The article aims to determine the paradigm in determining the quality of the hadith scholars, so as to know the strengths and weaknesses of each school and its implications for the use of the legal basis in the daily life of Muslims today.The findings of this study are as follows: a). There are four schools in determining the quality of the hadith scholars, namely, mutasyaddid (sstrict), muta’annut (excessive), mutawassit (moderate) and mutasahhil (soft- permissive). B). Implications school differences in the quality of the lives of Muslim tradition for the school mutasyaddid (strict) that the hadith does not meet kaedah validity, can not be used as proof syar’iyyah. Likewise, schools mutawassit (moderate), unless there is the argument (Qur’an-hadith) more powerful as supporters. Muta’annut and mutasahhil, the schools tend to use quality hadith da’i> f especially to the virtue of charity and morals.